Association of serum chemokine (C–C motif) 21 and receptor (C–C motif) 7 with Hashimoto’s thyroiditis——a preliminary clinical investigation - Gui, Xiaoting; Li, Yuting; Weng, Yu; Liao, Jiaxin; Xiang, Chunli; Qi, Xing; Xun, Lizhang; Bai, Feng (Frontiers in Endocrinology, 2025)
ObjectiveTo investigate the associations of serum chemokine C–C motif 21 (CCL21) and chemokine C–C motif receptor 7 (CCR7) levels with the Hashimoto’s thyroiditis.MethodsWe recruited 244 subjects (183 with Hashimoto’s thyroiditis and 61 healthy controls) from the Second People’s Hospital of Huai’an City. Patients with Hashimoto’s thyroiditis were divided into three groups according to the type of thyroid autoantibody: a. Double-positive group [elevated both thyroglobulin antibody (TgAb) and thyroid peroxidase antibody (TPOAb)]; b. TgAb group (elevated TgAb only); c. TPOAb group (elevated TPOAb only), they were further stratified according to thyroid function. We analyzed the between-group differences in the serum CCL21 and CCR7 levels which were quantified by enzyme-linked immunosorbent assay in all subjects.ResultsCompared with the healthy control group, the Hashimoto’s thyroiditis group had significantly increased serum CCL21 [154.92 (147.01, 165.34) vs 123.74 (118.02,129.22), p<0.001] and CCR7 [19.15 (18.19, 19.71) vs 16.47 (15.88, 17.14), p<0.001], decreased free triiodothyronine, and increased thyroid stimulating hormone, TgAb, and TPOAb. Correlation analysis revealed that serum CCL21 levels were positively correlated with TgAb and TPOAb levels. Univariate binary logistic regression analysis showed that elevated serum CCL21 [OR = 2.944, 95% CI (1.464, 5.919), p=0.002] was significantly associated with Hashimoto’s thyroiditis. The results of receiver operating characteristic curve analysis indicated that CCL21 has value for the diagnosis of Hashimoto’s thyroiditis [AUC (95% CI)=0.998 (0.996-1.000), p<0.001]. Subgroup analysis suggested that serum CCL21 levels were significantly higher in the double-positive group than in the TgAb and TPOAb groups.ConclusionSerum CCL21 is significantly elevated in patients with Hashimoto’s thyroiditis and correlates with both TgAb and TPOAb levels, suggesting that it is closely related to Hashimoto’s thyroiditis.